2013
DOI: 10.1002/cne.23284
|View full text |Cite
|
Sign up to set email alerts
|

Functional and neurochemical development in the normal and degenerating mouse retina

Abstract: The rd1 mouse is a well-established animal model for human retinitis pigmentosa (RP). We used electroretinography (ERG) to evaluate retinal function and postembedding immunocytochemistry to determine the changes in cellular amino acid expression in the normal (C57Bl6) and degenerating mouse retina (rd1), as a function of age during development and the onset of degeneration. In the normal mouse retina, photoreceptoral and post-photoreceptoral ERG responses improved simultaneously from eye-opening until adult le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 90 publications
(115 reference statements)
9
54
0
Order By: Relevance
“…In rd1 mice, the ERG response begins to reduce after eye opening, and becomes undetectable at around P21 [29]. In this study, we found that at P18, the normal ERG of C57 mice could be detected (Fig.…”
Section: Resultsmentioning
confidence: 49%
See 3 more Smart Citations
“…In rd1 mice, the ERG response begins to reduce after eye opening, and becomes undetectable at around P21 [29]. In this study, we found that at P18, the normal ERG of C57 mice could be detected (Fig.…”
Section: Resultsmentioning
confidence: 49%
“…1E). In rd1 mice, the apoptosis of rod cells usually appears at P8 and peaks at P14 [29, 30]. In this study, the number of apoptotic cells in the ONL of DMSO-treated rd1 mice at P14 significantly increased compared with age-matched C57 mice (P<0.001; Fig.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…3). To determine the relationship between photoreceptors and inner retinal neurons, the ratio of the b-wave to a-wave amplitude at the highest light intensity was determined for each individual animal then presented as the mean ± SEM (Gibson et al, 2013). Representative ERG traces before (grey line) and 1 h after (black line) administration of 5Â (7.25 mg/kg), 10Â (14.5 mg/kg) or 50Â (72.5 mg/kg) the normal maximum sildenafil dose.…”
Section: Erg Data Analysismentioning
confidence: 99%